1989
DOI: 10.1111/j.1365-2559.1989.tb01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant hepatic angiomyolipoma

Abstract: Pur/iolo,y.y, Tumours of the cardiovascular system. 2nd series, fasicle 15. Washington, DC: Armed Forces Institute of Pathology, 1978. ROBINSON FC. Aneurysms of the coronary arteries. Am. Hmi-I J . 1985; 109; 129 135. ROH LS. PAPARO GP. Primary malignant lym-phoma of the heart in sudden unexpected death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 2 publications
1
24
0
Order By: Relevance
“…A summary of these cases is shown in Table 1. Although, as Nonomura et al [7] reported, 24 of 39 (62%) hepatic AMLs with an invasive growth pattern into the surrounding parenchyma and along the portal and hepatic veins showed no malignant behavior, there were more than 9 cases of AML which may have had malignant potential [3,[8][9][10][11][12][13][14][15]. Our further review of these nine cases revealed that although an invasive pattern was found in almost all cases, 3 of 4 cases (Cases 2, 6-8) [9,[13][14][15] which showed portal vein thrombosis had a significantly severe prognosis, with 75% mortality, caused by multiple recurrences and metastases in the liver (Cases 2, 7, 8), peritoneum (Cases 2, 7), retroperitoneal region (Case 7), gastrohepatic omentum (Case 7), pancreas (Case 8), and lung (Case 8) [9,14,15].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A summary of these cases is shown in Table 1. Although, as Nonomura et al [7] reported, 24 of 39 (62%) hepatic AMLs with an invasive growth pattern into the surrounding parenchyma and along the portal and hepatic veins showed no malignant behavior, there were more than 9 cases of AML which may have had malignant potential [3,[8][9][10][11][12][13][14][15]. Our further review of these nine cases revealed that although an invasive pattern was found in almost all cases, 3 of 4 cases (Cases 2, 6-8) [9,[13][14][15] which showed portal vein thrombosis had a significantly severe prognosis, with 75% mortality, caused by multiple recurrences and metastases in the liver (Cases 2, 7, 8), peritoneum (Cases 2, 7), retroperitoneal region (Case 7), gastrohepatic omentum (Case 7), pancreas (Case 8), and lung (Case 8) [9,14,15].…”
Section: Discussionmentioning
confidence: 97%
“…Misdiagnosis of this tumor has been focused on in various articles; however, since 2000, several reports have revealed that hepatic AMLs can become malignant, metastasize, enlarge, and recur [3,5,[8][9][10][11][12][13][14][15]. In 1989, Ohmori et al [8] reported the first possibly malignant case, which increased in size to 18 cm and caused liver dysfunction and bronchopneumonia with exacerbating hepatomegaly, resulting in the patient's death. Dalle et al [9] reported a case in a 70-yearold woman, in whom the tumor showed a size increase from 15 to 26 cm in 5 years and metastasis in the lower abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…In 20 of these the cross-sectional imaging findings were reported [2, 4-8, 11, 13, 16-18, 25-28], whereas the other 29 were published in surgical or pathologic papers [9,10,12,14,15,[19][20][21][22][23][24][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Since this benign tumor was first described by Ishak in 1976 (1), only 52 cases have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Patients with these tumors did not usually manifest clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%